PERAN MASYARAKAT DALAM MENINGKATKAN KEBERSIHAN LINGKUNGAN DI SEKITAR TPA DESA PALEM RAYA KABUPATEN OGAN ILIR - Nadia Afifa; Azizah Husin; Erna Retna Safitri; Ardi Saputra (STKIP Subang, 2026)
This study aims to analyze the community's role in improving environmental cleanliness around the Palem Raya Village Landfill (TPA) in Ogan Ilir Regency using a descriptive qualitative approach. Seven informants participated in the study, and data were collected through interviews, observation, and documentation. Data analysis was conducted through data reduction, presentation, and triangulation. The results indicate that community contributions are still suboptimal. Material participation is voluntary, non-material participation is still individual, action participation is limited to household cleanliness, and social participation is low due to the lack of collective activities by the village government. Thus, community contributions tend to be passive, and efforts are needed to increase more active and organized participation.